A Phonological Analysis on the English Consonants of Sundanese EFL Speakers - Faizal Risdianto (Penerbit STKIP PGRI Bangkalan, 2017)
This descriptive qualitative study focuses on the description of the English consonants systems spoken by speakers of Sundanese backgrounds. This implies that such speakers of particular regional backgrounds speak unique and ideosyncratic native languages. This study will provide a description on the consonants production of English as Foreign Language (EFL) speakers with Sundanese native language in an experimental phonetic method to the students of Islamic Education Department of State Institute for Islamic Studies Salatiga. In this study, the writer have two objectives: (1) to know the English consonants systems of EFL Sundanese speakers in Islamic Education Department of State Institute for Islamic Studies Salatiga? and (2) to know the most frequent errors on pronouncing English consonants produced by EFL Sundanese speakers. From the result of the analysis, it can be seen that the EFL Sundanese students made 262 errors. It can also been seen that the greatest errors made by the EFL Sundanese students are mispronouncing the minimal pairs of /f/ and /v/, /s/ and /Ó¨/ and /Ã°/ and /z/. The misuse of the sound â€œpâ€ instead of â€œbâ€ is common error for Sundanese since there is not distinction between the sound â€œfâ€, â€œvâ€ dan â€œpâ€ in sundanese phonological system